Chaperone protein HSC70 regulates intercellular transfer of Y chromosome antigen DBY - Kretschmann, Sascha; Herda, Stefanie; Bruns, Heiko; Russ, Josefine; van der Meijden, Edith D.; Schlötzer-Schrehardt, Ursula; Griffioen, Marieke; Na, Il Kang; Mackensen, Andreas; Kremer, Anita (Journal of Clinical Investigation, 2019)
Recent studies have demonstrated that CD4+ T cells can efficiently reject MHC-II-negative tumors. This requires indirect presentation of tumor-associated antigens on surrounding antigen-presenting cells. We hypothesized that intercellular transfer of proteins is not the sole consequence of cell death-mediated protein release, but depends on heat-shock cognate protein 70 (HSC70) and its KFERQ-like binding motif on substrate proteins. Using human Y chromosome antigen DBY, we showed that mutation of one of its 2 putative binding motifs markedly diminished T cell activation after indirect presentation and reduced protein-protein interaction with HSC70. Intercellular antigen transfer was shown to be independent of cell-cell contact, but relied on engulfment within secreted microvesicles. In vivo, alterations of the homologous KFERQ-like motif in murine DBY hampered tumor rejection, T cell activation, and migration into the tumor and substantially impaired survival. Collectively, we show that intercellular antigen transfer of DBY is tightly regulated via binding to HSC70 and that this mechanism influences recognition and rejection of MHC-II-negative tumors in vivo.
CRIS-Team Scopus Importer:2019-07-09
Keywords: Antigen presentation; Cancer immunotherapy; Immunology; Oncology; T cells